Association of DVWA rs11718863 Gene Polymorphism with Knee Osteoarthritis in Iraqi Patients (Iraqi Journal of Medical Sciences, 2022)
Background: Osteoarthritis (OA) is a complex degenerative articular disease that has an ambiguous pathogeny because variant risk factors participate in the process of cartilage deterioration. Genetic factors may have a role in the onset and progression of OA.Objective: To investigate potential association between severity of knee OA (KOA) and Double von Willebrand factor A domains DVWA rs11718863 gene polymorphism.Methods: One hundred and twenty Iraqi patients diagnosed with KOA, aged (45 years and above) and sixty healthy people (control) at the same age range, with no family history of OA were evaluated at Al-Imamein Al-Kadhimein Medical City (Rheumatology Department). The degree of severity of KOA was assessed by clinical and radiographic assessment. DVWA rs11718863 genotyping was performed using DNA sequencing (Sanger’s method).Results: Two different genotypes wild homozygote (TT) genotype and heterozygote (AT) appeared by genotyping of DVWArs:11718863. Highly significant difference (p
Keywords: Double von Willebrand factor A domains DVWA; single nucleotide polymorphism SNP; body mass index; Knee osteoarthritis; KOA